Melengkapi Teori Akses dengan Pendekatan Kolaboratif dalam Konteks Perhutanan Sosial di Indonesia - Dicky Rachmawan; Francisia Saveria Sika Ery Seda; Robert Siburian (Jurnal Masyarakat dan Budaya, 2021)
Many previous studies examine social forestry in Indonesia from 2016-2020 which describing the factors relate to the implementation. Beyond the previous studies, this paper clustering and mapping the factors through access theory and further complement access theory by a collaborative approach in the social forestry implementation context. Qualitative desk research is used to examine 39 papers with Nvivo 12. The result shows there are two elements of the four elements of structure-relational access mechanism (SRAM) that have positive effects on social forestry implementation, while three elements of the five elements of the SRAM element give a negative effect. In turn, there are various unclustered factors which not a part of SRAM that affects social forestry implementation both positive or negative. These unclustered factors are the blank spaces of access theory which complemented by a collaborative approach, there are “participation” and “equity” which supported by “effective communication”. With a collaborative approach, the scope becomes wider that not only analyze in individual scope, but also in organizational scope, and the benefit can be seen by outside stakeholder through community contribution in social forestry implementation.